RELATIONSHIP OF LIPIDS, C-REACTIVE PROTEIN AND SIALIC ACID IN THE HEALTHY INDIVIDUALS - Israr, Mohammad; Gul, Chaman; Rehman, Aziz ur; Khan, Abdus Sattar; Siyar, Muhammad; Rahim, Salma; Arshad, Muhammad (Journal of Ayub Medical College Abbottabad, 2018)
Background: Raised levels of cholesterol and triglycerides are major risk factors for atherosclerosis, which can lead to coronary heart disease. Both the CRP and Sialic Acid levels are elevated in response to acute as well as chronic inflammatory conditions. This study was conducted to determine the serum lipid profile, CRP and Sialic Acid levels and their relationship with each other in healthy individuals. Methods: This was a cross-sectional study performed by the Department of Biochemistry, Institute of Basic Medical Sciences (IBMS), Khyber Medical University (KMU) Peshawar. Two hundred healthy subjects in the age group of 18-50 years of either gender were recruited through consecutive sampling. Blood sampling were taken from all the participants and analysed each for serum lipid profile, CRP and Sialic Acid levels through standardized methods. Results: A total of 200 individuals were included, 53.5% being male. Mean age was 33.39±9.76 years. Mean height was 167.86±10.8 cm. Mean weight was 66.87±11.39kg. Mean Hip-Waist ratio was 0.93±0.16 whereas mean BMI was 24.12±3.65. The simultaneous raised levels of serum lipids, CRP and Sialic Acid were observed more commonly in females as compared to males. CRP and Sialic Acid has got statistically significant correlation with HDL. Sialic Acid had statistically significant correlation with triglycerides in the study population with a significant p-value (<0.05), while having a non-significant correlation with total cholesterol and LDL. CRP had got significant correlation with total cholesterol and LDL and non-significant correlation with triglycerides. Conclusion: The study showed that serum CRP and Sialic Acid had a significant negative correlation with serum HDL. A significant positive correlation was found between serum Sialic Acid and triglycerides. CRP and Sialic Acid though expensive but are useful predictors of atherosclerotic disease. Keywords: Triglycerides; HDL; LDL; Cholesterol; CRP; Sialic Acid